2019
DOI: 10.1063/1.5093425
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic effect of nanodiamonds on the adsorption of tricresyl phosphate on iron oxide surfaces

Abstract: Nanodiamonds (NDs) have potential uses in many applications, including as additives for liquid lubricants, where they may be combined with more traditional chemicals to form protective films on sliding surfaces. It has been shown that NDs can function synergystically with tri-cresyl phosphate (TCP) to facilitate film formation on air baked iron. Here, reactive molecular dynamics simulations of TCP and NDs on an amorphous iron oxide surface reproduce experimental observations of the temperature at which film fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…67 The ReaxFF parameter set has previously been applied to study the thermal decomposition of TCP on a-Fe3O4-OH surfaces 36 as well as TCP interactions with nanodiamonds on the same surface. 37…”
Section: Force Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…67 The ReaxFF parameter set has previously been applied to study the thermal decomposition of TCP on a-Fe3O4-OH surfaces 36 as well as TCP interactions with nanodiamonds on the same surface. 37…”
Section: Force Fieldmentioning
confidence: 99%
“…Initially, the energy of each system was minimised using the conjugate gradient method, followed by equilibration for 0.2 ns at 300 K. Then, the temperature was linearly increased from 300 to 1000 K over 1.4 ns (heating rate of 0.5 K ps -1 ). 37 The selected temperature range is representative of that experienced by phosphate esters when they are used as VPLs under UHV conditions 9 and antiwear additives under EP conditions. 80 Previous ReaxFF studies of hydrazine molecules showed that, as the heating rate was increased from 50 to 200 K ps -1 , the onset temperature for decomposition increased from 1350 to 1690 K. 62 Although the heating rate used here is relatively low by ReaxFF simulation standards, it is still several orders of magnitude higher than that applied experimentally (ca.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the energy of each system was minimised using the conjugate gradient method, followed by equilibration for 0.2 ns at 300 K. Then, the temperature was linearly increased from 300 to 1000 K over 1.4 ns (heating rate of 0.5 K ps -1 ). 37 The selected temperature range is representative of that experienced by phosphate esters when they are used as VPLs under UHV conditions 9 and antiwear additives under EP conditions. 80 Previous ReaxFF studies of hydrazine molecules showed that, as the heating rate was increased from 50 to 200 K ps -1 , the onset temperature for decomposition increased from 1350 to 1690 K. 62 Although the heating rate used here is relatively low by ReaxFF simulation standards, it is still several orders of magnitude higher than that applied experimentally (ca.…”
Section: Simulationsmentioning
confidence: 99%